THE IMPLEMENTATION OF TEACHER COMPETENCE ON 21ST CENTURY IN INDONESIA ELEMENTARY SCHOOL - Desi Rahmawati; Rugaiyah Rugaiyah; Cecep Kustandi (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2022)
The purpose of this research is to explain how to improve teacher’s skill that must-have in the 21st century, which includes critical thinking skill, collaboration, communication and creativity. The subject of this research were several principals and teachers of Elementary Schools in the East Jakarta, include state or private school, with 15 principals and 15 teachers as participants. This research uses a qualitative approach with case study method, and data collection from interviews, questionnaire, observation and documentation. The result of this research shows that principals and teachers have made efforts to develop teacher competencies in the 21st century, in the aspects of critical thinking, creativity, communication, and collaboration skills.